EKOP Model of Islamic Cultural History (SKI) Learning for Islamic Religious Education Teacher Candidates - Romelah Romelah; Eka Firmansyah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Evaluation is inseparable from learning; the essence of learning is a conscious effort by students to meet needs that result in changes in themselves across cognitive, affective, and psychomotor aspects. This study examines the process and results of the evaluation of Islamic Cultural History (SKI) learning in the Islamic Religious Education Study Program, Faculty of Islamic Religion, University of Muhammadiyah Malang. Using a qualitative case-study approach, this study involved 12 students from batch V A in 2019 as informants. Data collection methods include observation, interviews, and documentation, with data analysis using the Miles and Huberman models. The focus of the research consists of three main aspects: (1) learning planning through the Semester Learning Plan, (2) the implementation of online and offline learning, and (3) learning evaluation, both written and oral, and assignments. The results of the study describe the evaluation process that includes students' cognitive, affective, and psychomotor abilities in mastering the concept of SKI, including the ability to search for movies and make images related to the material. This research aims to produce final reports and scientific articles for publication in reputable international journals. The findings of the study are expected to provide insight into the adaptation of SKI learning during the pandemic and the effectiveness of the evaluation methods applied.